Regulatory T cell therapy suppresses inflammation of oral mucosa - Xue, Ningning; Wang, Ying; Cheng, Hao; Liang, Hantian; Fan, Xinzou; Zuo, Fengqiong; Zeng, Xin; Ji, Ning; Chen, Qianming (Frontiers in Immunology, 2022)
Oral inflammatory diseases, including oral lichen planus (OLP) and recurrent aphthous ulcer (RAU), seriously affect the patient’s quality of life. Due to the lack of ideal disease models, it is difficult to determine whether novel immunotherapy strategies are effective in treating oral inflammatory diseases. Here, we show that the deficiency of Foxp3 or IL-2 caused oral mucosa inflammation in mice, proving that Treg cells are important in maintaining the immune homeostasis in the oral mucosa. Then we determined that adoptive transfer of CD4+CD25-CD45Rbhigh T cells could induce oral inflammation in Rag1-/- mice, and co-transfer of Treg cells together with CD4+CD25-CD45Rbhigh T cells could suppress the development of oral inflammation in this mouse model. Our study showed that adoptive transfer of CD4+CD25-CD45Rbhigh T cells into Rag1-/- mice could be a novel disease model of oral inflammation. Our data provides direct evidence that Treg cell therapy is effective in suppressing oral mucosa inflammation in mice. Therefore, Treg cell therapy may be a promising novel strategy to treat oral inflammatory diseases.